The Verb “Memukul’ in the Balinese Language Dialect Spoken at Taro Village: A Natural Semantic Metalanguage Study (e-Journal of Linguistics, 2020)
The people living at Taro village speak the Balinese languageas their daily language. As the speakers of the Balineselanguge, they never neglect the speech order, as can be seenfrom the fact that they still use the Balinese words, which in themodern era, have been neglected, resulting in the fact that manypeople are not familiar with a number of words, especiallythose which belong to the verb word class, one of which is theverb “ngetok” (hit). The Balinese language has a great numberof verbs; however, the current study only analyses the verb“ngetok’ (hit) using the theory of Natural MetalanguageSemantics (NMS). The verb “ngetok” (hit) has a great numberof equivalents; they are ngebug, ngedig, nigtig, ngupek,megambel, mugpugin, mukpukin, ngukul, nungting, ngempug,nyakcak, noktok, ngeplokin, nebuk, ngaasin, nepung, ngintuk,ngalocok, namplak, nyemés, nempéléng, nyagur, nyepédin,nglamet, ngamplongin, ngamplengin, ngemplangin,nglentangin, ngaplekin, nyontok, nylimed and mentil. One verbis different from another, although they are all used to expressthe action of hitting something or someone, depending on whattool is used to hit and the subject and object which are hit. Theverb “ngetok” (hit) in the Balinese language has two differentmeanings; namely doing something and taking place, which canbe explained using the explication technique in which it isdescribed that “X does something on Y, causing somethingeither bad or good to occur to Y”. Such differences in meaningcan be obtained through the analysis of the original meaningusing the non-compositional polysemy.
Keywords: the Verb of “Ngetok”; dialect; Natural Semantic Metalanguage